Perbaikan Proses Bisnis Keripik Pisang menggunakan Lean Business Model Canvas di PT. Dwihanz Sinergi Utama Sidoarjo - Setyo, Wawan; Handriyanto, Bamban; Arfianto, Teguh; Wahyuningtias, Novi; Hariastuti, Ni Luh Putu; Daryanto, Daryanto (JURMATIS (Jurnal Manajemen Teknologi dan Teknik Industri), 2024)
Banana chips are one of the popular processed fruit products in foreign markets, such as in Australia, Singapore, and New Zealand. Research to improve optimal business processes. The research procedure reduced data through the analysis of interviews with five informants using BMC and LBMC to find the root of the problem as a guide. On improving business processes with the power of LBMC, the priority here is to find activities that are minimum mandatory to form value for customers. Revenue streams at LBMC include direct sales through its website or physical stores, wholesale partnerships with health food stores, gyms, and gyms, online marketplaces like Amazon or Shopee, as well as collaborations with airlines, hotels, and other hospitality businesses for in-flight snack options. This research contributes to the understanding of business process improvement in the food industry by providing practical insights in identifying customer segments, channels to reach them, cost structures, and revenue streams